PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI MELALUI LINGKUNGAN KERJA PADA KANTOR DINAS PERHUBUNGAN PROVINSI SUMATRA UTARA - Werlina giawa; Didikarniwati Gulo; Khairuddin Tampubolon (Jurnal Genta Mulia, 2024)
The aim of this research is to determine the influence of the organization on employee performance through the work environment at the North Sumarera Province Transportation Agency using a quantitative Ex Post Facto research approach. The results obtained are that the variable t-value of organizational culture (x1) is 7.417, which is greater than the t-table 2.003 and the sig value is 0.000<0.05, which means that the organizational culture variable (x1) has a significant and significant influence on the performance of employees of the North Sumatra transportation service office. Accepted. The results obtained are a t-count variable work environment value (x2) of 7.477 which is greater than t table 2.003 and a sig value of 0.000 <0.05, which means that the work environment variable (x2) has a significant and significant effect on the performance of employees of the North Sumatra Transportation Service Office. Accepted. Based on the table above, it shows that by looking at the coefficient value of each independent variable or independent variable, namely organizational culture (X1) and work environment (x2). Organizational culture has a regression coefficient value of 0.319 and the work environment has a regression coefficient of 0.563, or a beta value of 0.506 <0.510. It can be concluded that the work environment variable has a big influence on employee performance because it has a higher regression coefficient.